Assessing the impact of health research on health policies: a study of the Dodowa Health Research Centre, Ghana - Escribano-Ferrer, Blanca (BMC Health Serv Res, 2017)
BACKGROUND: The importance of assessing research impact is increasingly recognised. Ghana has a long tradition of research dating from the 1970s. In the Ghana Health Service there are three health research centres under the Research and Development Division. Dodowa Health Research Centre (DHRC) is the youngest in the country dating from the 1990s. The objective of this study is to analyse the influence of the research conducted in DHRC on national and local health policies. METHODS: The study used the Research Impact Framework. Six projects were selected based on a set of criteria. Thirteen interviews were conducted with researchers and policy makers using a semi-structured interview guide. RESULTS: DHRC had numerous policy impacts in terms of researchers participating in policy networks, increasing political capital and influencing policy documents. Factors identified to be associated with policy impact included collaboration with policy makers at the design stage, addressing health priorities, and communicating results mainly through the participation in annual review meetings. CONCLUSIONS: DHRC was successful in influencing health policies. Recommendations were made that could be included in the DHRC strategic planning to improve the research process and its policy impact. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-017-2383-0) contains supplementary material, which is available to authorized users.